Clinical feature of Rett syndrome and MeCP2 genotype/phenotype correlation analysis - Bao, Xin-hua (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2004)
OBJECTIVE: Rett syndrome (RTT) is a neurodevelopmental disorder which causes severe mental retardation. This study aimed at elucidating clinical features of 66 Chinese RTT cases diagnosed by The Department of Pediatric Neurology, Peking University First Hospital since 1987, and at analysis of the MeCP2 genotype / phenotype correlation